Efficacy of the feed additive consisting of decoquinate (Deccox®) for use in chickens for fattening (Zoetis Belgium SA). (8th March 2021) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the efficacy of decoquinate (Deccox ® ) for chickens for fattening. In a former opinion adopted by the FEEDAP Panel, the potential of decoquinate to prevent coccidiosis in chickens for fattening could not be established due to insufficient evidence. In the present assessment, the applicant submitted new efficacy studies in chickens for fattening to address the data gaps identified in the previous opinion. In addition, the applicant proposed to increase the minimum of the dose range from 20 mg decoquinate/kg complete feed to 30 mg/kg. The coccidiostatic efficacy of decoquinate from Deccox ® in chickens for fattening was shown in three floor pen studies at a level of 30 mg decoquinate/kg complete feed. Considering the results of three anticoccidial sensitivity tests (ASTs) with 30 mg decoquinate/kg complete feed for chickens for fattening already described and assessed in a previous FEEDAP opinion and taking into account the newly submitted floor pen data with 30 mg decoquinate/kg complete feed, the FEEDAP Panel concludes that decoquinate from Deccox ® is effective in controlling coccidiosis in chickens for fattening at a minimum dose of 30 mg/kg complete feed.